OPTIMIZING SOCIAL MEDIA FOR THE MARKETING OF SMES PRODUCTS AT AL-FATIMAH ISLAMIC BOARDING SCHOOL BOJONEGORO - Saummita, Tyas Wulandari; Sholikhah, Ayu Putri Nur; Segara, Nuansa Bayu (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lambung Mangkurat, 2023)
Facing advancements in the digital era, micro, small, and medium-sized enterprises (SMEs) need to keep up with technological developments to remain competitive in the marketing world. Social media is one of the platforms that can be effectively utilized to digitally market products, making them accessible to a wider audience. The marketing of products from Al-Fatimah Islamic Boarding School Bojonegoro SMEs has not fully utilized social media. This article aims to propose optimal social media strategies for marketing SMEs products at Al-Fatimah Islamic Boarding School Bojonegoro. The research approach used is qualitative research with a case study method. Data is obtained through interviews with the managers of SMEs at Al-Fatimah Islamic Boarding Scholl, observation of the marketing activities already carried out, and an analysis of literature related to marketing through social media. The results of this research offer a solution by optimizing social media to enhance the marketing of SMEs products at Al-Fatimah Islamic Boarding School Bojonegoro. Practical recommendations are also provided regarding the use of specific social media platforms and promotional methods that can be implemented to expand product marketing.